PENGARUH PENDIDIKAN AGAMA KRISTEN TERHADAP UPAYA MEMINIMALISASI SIKAP HIDUP HEDONISME KELAS XI DI SMA NEGERI 5 MEDAN - Arnita Simanjuntak; Nurliani Siregar; Udur Ernita Aritonang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine and analyze the influence of Christian Religious Education in efforts to minimize hedonistic lifestyles among Grade XI students at State Senior High School 5 Medan. The background of this research is based on the phenomenon of the increasing tendency of hedonistic lifestyles among teenagers, which is influenced by the development of technology, social media, and peer environments. A lifestyle that is oriented toward pleasure, luxury, and excessive self-satisfaction can affect students’ character, moral values, and spiritual life. In this context, Christian Religious Education plays an important role in instilling values of faith, morality, and Christian ethics that can shape a more modest, responsible lifestyle based on biblical teachings.The research method used in this study is descriptive with a qualitative approach. Data collection techniques were carried out through observation, interviews, and documentation. The collected data were then analyzed using an interactive analysis model which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that Christian Religious Education has a significant influence in helping minimize hedonistic lifestyles among students. Through the teaching of Christian values, the teaching of God's Word, spiritual discussions, and character development, students gain a better understanding of the importance of living simply, exercising self-control, and prioritizing spiritual values over worldly pleasures. In addition, Christian Religious Education also helps students develop moral and spiritual awareness so that they are able to face negative influences from the environment and the development of modern culture.